2013
DOI: 10.1007/s10689-013-9682-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breast cancer family history on tumor detection and tumor size in women newly-diagnosed with invasive breast cancer

Abstract: This study evaluated the impact of family history (FH) on tumor detection, the patient's age and tumor size at diagnosis in breast cancer (BC). Furthermore, we investigated whether the impact of FH on these features was dependent on degree of relationship, number of relatives with a BC history, or the age of the affected relative at the time that her BC was diagnosed. Out of the entire cohort (n = 1,037), 244 patients (23.5%) had a positive FH; 159 (15.3%) had first-degree relatives affected with BC and 85 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Breast cancer screening behavior evaluation form: breast cancer screening behaviors were evaluated by a structured questionnaire prepared by the researchers based on a literature review (14,20). This form consisted of questions regarding regular BSE in the last 6 months, getting CBE in the last year and undergoing mammography in the last year as evaluated using yes/no answers.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer screening behavior evaluation form: breast cancer screening behaviors were evaluated by a structured questionnaire prepared by the researchers based on a literature review (14,20). This form consisted of questions regarding regular BSE in the last 6 months, getting CBE in the last year and undergoing mammography in the last year as evaluated using yes/no answers.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Every year, many women die because of breast cancer, which illustrates the importance of screening in reduction of breast cancer-related deaths (1). Schwab et al (14) reported that better results were achieved regarding tumor size, disease phase and histological examination through screening programs in women with breast cancer. In a study conducted in Turkey (15), groups having higher risk for breast cancer had mammography rates 11 times higher than the others and in another study, it was determined that the CBE rate was 48.1% in women with a family history (16).…”
mentioning
confidence: 99%
“…Only around 24% of the familial risk of BC can be attributed to known risk-increasing mutations such as BRCA1 and BRCA2 [15]. There is evidence that family history of breast cancer is associated with an increased awareness of BC, more frequent radiologic examinations and early detection of BC [16], but not a worse prognosis [17,18].…”
Section: Family History Of Bcmentioning
confidence: 99%
“…Breast cancer is a multifactorial disease that involves a complex combination of genetic and environmental factors. A positive family history of breast cancer increases the risk of developing this disease; this neoplasm is twice as common in women with affected first-degree relatives [3, 4]. It is estimated that most cases of this cancer are spontaneous; only 15 to 20% of cases are familial and associated with germline mutations in genes involved in the detection and repair of DNA damage [5].…”
Section: Introductionmentioning
confidence: 99%